Follow-up of cerebral aneurysm embolization with hydrogel embolic system: Systematic review and meta-analysis. Issue 10 (October 2015) - Serafin, Zbigniew; Di Leo, Giovanni; Pałys, Alicja; Nowaczewska, Magdalena; Beuth, Wojciech; Sardanelli, Francesco
Abstract: Background: Hydrogel embolic system (HES) for endovascular treatment of cerebral aneurysms was developed to reduce the risk of aneurysm recurrence and the rate of retreatment. The aim of this systematic review was to verify the efficacy of HES, also in comparison to bare platinum coils (BPC). Material and methods: A systematic literature search was performed by two independent reviewers for articles published until January 31st, 2013 on the follow-up recurrence rate of intracranial aneurysm embolization with hydrogel-coated coils. Results: Thirteen articles on the use of HES for embolization of cerebral aneurysms were included in this study, for a total of 1683 embolized aneurysms. Significant heterogeneity was found regarding patient populations, methods of aneurysm coiling, follow-up schedules, and recurrence definitions. The pooled rate of initial complete aneurysm occlusion was 55% (95%CI, 38–70%); 59% (95%CI, 43–74%) in the subgroup of aneurysms treated with the use of HES. The pooled total recurrence rate was 19% (95%CI, 15–24%); 17% (95%CI, 14–22%) in the HES-treated subgroup. The pooled major recurrence rate was 12% (95%CI, 8–18%); 11% (95%CI, 7–16%) in the HES-treated subgroup. Comparing both types of coils, the pooled odds ratio for total recurrence was 0.63 (95%CI, 0.45–0.88; p = 0.008) in favor of HES. Conclusions: Embolization of cerebral aneurysms using HES seems to result in a lower rate of recurrence than that obtained using BPC, which is in line with the only randomized controlled trial. High-quality prospective studies are needed to define specific indications for the use of hydrogel-coated coils.